[Results from the 'Ethiopia-Netherlands AIDS Research Project'; 1995-2000] - de Wit, T; Sanders, E; Fontanet, A; Goudsmit, J; Miedema, F; Coutinho, R (2001)
Since 1995 the 'Ethiopia-Netherlands aids research project' (ENARP) has been up and running in Addis Ababa, Ethiopia. Several surveys point towards an HIV seroprevalence of approximately 15% amongst adult Ethiopians in the capital city. Prospective cohort studies initiated since early 1997 indicate that healthy, HIV negative Ethiopians have lower CD4+ T-cell counts compared to the Dutch population and in addition they have chronically activated immune systems, possibly as a result of the highly prevalent intestinal parasitic infections as well as other infections. HIV positive Ethiopians are mainly infected with HIV-1 subtype C, which can be subdivided in 2 subtypes, both of which entered Ethiopia in the early 1980's. There are considerable differences between Ethiopians and Dutch in terms of biomedical parameters relevant for HIV infection progression; these justify further efforts in future scientific research. The emphasis for this should be on robust and applicable laboratory methods, research in the field of HIV vaccine trials and information transfer to the various partners combating HIV infection/aids in Ethiopia.